2021
DOI: 10.3390/ph14070639
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Drugs for Intra-Arterial Treatment of Colorectal Cancer Liver Metastases: In-Vitro Screening after Short Exposure Time

Abstract: To treat colorectal liver metastases, intra-arterial chemotherapies may complete therapeutic arsenal. Drugs using intra-arterially are very heterogeneous. The aim of this study was to select the most efficient drug on a panel of colorectal cancer (CRC) cell lines (Caco-2, HCT 116, HT 29, SW 48, SW 480, SW 620) exposed for 30 min to 12 cytotoxic agents (doxorubicin, epirubicin, idarubicin, 5-FU, raltitrexed, gemcitabine, cisplatin, oxaliplatin, mitomycin C, irinotecan, streptozocin, paclitaxel) at different con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
(57 reference statements)
2
7
0
Order By: Relevance
“…We described the synthesis and data obtained with fifty-two compounds based on 3 ,4 ,5 -trimethoxyaniline (7a-ad) and variably substituted anilines (8a-v) at the 7-position of the 2-substituted- [1,2,4]triazolo [1,5-a]pyrimidine nucleus. Thirty-six of the fifty-two synthesized compounds showed antiproliferative activity against human colon adenocarci-noma HT-29 cells superior to that of CA-4, with 7n, 8q-s and 8u-v possessing the highest overall potency, with IC 50 values lower than 100 nm (49-83 nM), comparable with the data reported in the literature for the most commonly used cytotoxic agents (oxaliplatin, raltitrexed and irinotecan) in the treatment of colorectal cancer (CRC) [58]. The typical resistance of the colorectal carcinoma cell line HT-29 against CA-4 and analogous compounds bearing a phenolic group (R=OH) on the B-ring was previously reported to be partly mediated by an overexpression of the MRP-1 and MRP-3 efflux transporter [59].…”
Section: Discussionsupporting
confidence: 75%
“…We described the synthesis and data obtained with fifty-two compounds based on 3 ,4 ,5 -trimethoxyaniline (7a-ad) and variably substituted anilines (8a-v) at the 7-position of the 2-substituted- [1,2,4]triazolo [1,5-a]pyrimidine nucleus. Thirty-six of the fifty-two synthesized compounds showed antiproliferative activity against human colon adenocarci-noma HT-29 cells superior to that of CA-4, with 7n, 8q-s and 8u-v possessing the highest overall potency, with IC 50 values lower than 100 nm (49-83 nM), comparable with the data reported in the literature for the most commonly used cytotoxic agents (oxaliplatin, raltitrexed and irinotecan) in the treatment of colorectal cancer (CRC) [58]. The typical resistance of the colorectal carcinoma cell line HT-29 against CA-4 and analogous compounds bearing a phenolic group (R=OH) on the B-ring was previously reported to be partly mediated by an overexpression of the MRP-1 and MRP-3 efflux transporter [59].…”
Section: Discussionsupporting
confidence: 75%
“…We used PT1 as an example for which we tried to further identify effective drugs simultaneously based on prediction results and prior knowledge. Previously, topoisomerase inhibitors targeting TOP2A were reported to be sensitive drugs for CMS-4 that PT1 belongs to ( Sveen et al, 2018 ; Carvalho et al, 2021 ; Fohlen et al, 2021 ), and we did find that PT1 showed parent sensitivity (sRGES < -0.1) to four of the eight topoisomerase inhibitors targeting TOP2A (mean sRGES was -0.11, and the mean rank was 78) ( Figure 4D ). We used the PT1-related cell line (HCC-56) to further filter effective drugs.…”
Section: Resultsmentioning
confidence: 50%
“…PLK4-siRNA (50 pM) and NC-siRNA (50 pM) were respectively transfected into the HCT-116 and the LoVo cells using Lipofectamine™ 2000 Transfection Reagent (Thermo Fisher Scientific, Inc.) at 37˚C for 48 h. Following transfection, the cells in each cell line were categorized as PLK4-siRNA, NC-siRNA and blank control cells (without transfection). The cells were then treated with 5-FU (Merck KGaA) at the following concentrations: 0, 1, 2, 4, 8 and 16 µM for 48 h, which was based on previous studies with some modification (27,28). Following treatment, Cell Counting Kit-8 reagent (Beyotime Institute of Biotechnology) was added to the cells, followed by incubation at 37˚C for 2 h. Finally, absorbance was measured at 450 nm using a microplate reader, and cell viability at different concentrations of 5-FU was calculated.…”
Section: Methodsmentioning
confidence: 99%